2020
DOI: 10.3847/1538-4357/ab8f97
|View full text |Cite
|
Sign up to set email alerts
|

The Ionizing Photon Production Efficiency (ξion) of Lensed Dwarf Galaxies at z ∼ 2*

Abstract: We measure the ionizing photon production efficiency (ξ ion) of low-mass galaxies (10 7.8-10 9.8 M e) at 1.4<z<2.7 to better understand the contribution of dwarf galaxies to the ionizing background and reionization. We target galaxies that are magnified by strong-lensing galaxy clusters and use Keck/MOSFIRE to measure nebular emission-line fluxes and Hubble Space Telescope to measure the rest-UV and rest-optical photometry. We present two methods of stacking. First, we take the average of the log of Hα-to-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 93 publications
(178 reference statements)
2
49
0
Order By: Relevance
“…where N (H 0 ) is the ionizing photon rate in s −1 and L FUV is the luminosity density at 1500 Å in erg s −1 Hz −1 . ξ ion is typically constrained by combining dust-corrected Hα and FUV luminosities (e.g., Bouwens et al 2016a;Matthee et al 2017;Shivaei et al 2018;Emami et al 2020). In this work, ξ ion was computed directly from the best-fit intrinsic SPSneb model, a route that obviates the need to apply potentially uncertain dust corrections to Hα and FUV luminosities (Shivaei et al 2018), account for LyC photons that may escape the ISM or be absorbed by dust (Inoue 2001), or implement conversions between Hα luminosity and N (H 0 ) that may not apply to the galaxies in question (e.g., Reddy et al 2016b;Theios et al 2019).…”
Section: Quantifying the Shape Of The Ionizing Spectrummentioning
confidence: 99%
“…where N (H 0 ) is the ionizing photon rate in s −1 and L FUV is the luminosity density at 1500 Å in erg s −1 Hz −1 . ξ ion is typically constrained by combining dust-corrected Hα and FUV luminosities (e.g., Bouwens et al 2016a;Matthee et al 2017;Shivaei et al 2018;Emami et al 2020). In this work, ξ ion was computed directly from the best-fit intrinsic SPSneb model, a route that obviates the need to apply potentially uncertain dust corrections to Hα and FUV luminosities (Shivaei et al 2018), account for LyC photons that may escape the ISM or be absorbed by dust (Inoue 2001), or implement conversions between Hα luminosity and N (H 0 ) that may not apply to the galaxies in question (e.g., Reddy et al 2016b;Theios et al 2019).…”
Section: Quantifying the Shape Of The Ionizing Spectrummentioning
confidence: 99%
“…In this paper, we have derived the [OIII]𝜆5007 EW distribution in z 2 UV-selected galaxies, thereby quantifying the fraction of EELGs at z 2. Locally (z ∼ 0) and at intermediate redshifts (1 < z < 3), EELGs have been shown to be extremely efficient ionisers, both due to their large ionisation production efficiencies (Chevallard et al 2018;Tang et al 2019;Nakajima et al 2020;Emami et al 2020) and their large escape fractions (e.g. Jaskot et al 2019;Nakajima et al 2020;Izotov et al 2016;Vanzella et al 2016;Fletcher et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…8b, we show the relation Ne3O2 -O 32 for CSFGs (blue and red dots) (Shivaei et al 2018) for Calzetti et al (1994Calzetti et al ( , 2000 and SMC reddening laws are shown in (a) by green and magenta lines, respectively. Mean ξ ion values of z = 4 -5 galaxies (Lam et al 2019a) (Chevallard et al 2018), z ∼ 2 lensed galaxies (Emami et al 2020), and z ∼ 1.4 -3.8 galaxies (Reddy et al 2018), respectively; LAEs at z ∼ 3 (Nakajima et al 2020) and z ∼ 6.6 SFGs with Lyα emission (Endsley et al 2020) and z ∼ 2 MOSDEF SFGs (black-filled circles). Both Ne3O2 and O 32 were proposed by Levesque & Richardson (2014) as estimators for the ionisation parameter U in local SFGs.…”
Section: Stellar Mass and Metallicity Relationmentioning
confidence: 99%
“…Together with the escape fraction of ionising photons from galaxies, the ionising photon production efficiency ξ ion is one of the important parameters characterising the ability of highz SFGs to ionise the intergalactic medium during the epoch of reionisation at z > ∼ 6. The ionising photon production efficiency ξ ion has been derived in several studies for high-z SFGs, with log(ξ ion /[Hz erg −1 ]) values in the range of ∼ 25.1 -25.8 (Bouwens et al 2016;Harikane et al 2018;De Barros et al 2019;Shivaei et al 2018;Emami et al 2020). On the other hand, Maseda et al (2020) used a sample of 35 z ∼ 4 -5 continuum-faint LAEs and measured a very high log(ξ ion /[Hz erg −1 ]) = 26.28, implying a more efficient production of ionising photons in lower-luminosity Lyα selected galaxies, possibly produced by extremely low-metallicity stellar populations in very young starbursts.…”
Section: Relations Including the Ionising Photon Production Efficienc...mentioning
confidence: 99%